PROFILE OF TYPE 2 DIABETES MELLITUS IN ACUTE THROMBOTIC STROKE - Jordan, Danny Randy; Islamiyah, Wardah Rahmatul; Prayitno, Jongky Hendro (Malang Neurology Journal, 2019)
Background: Stroke is a brain disorder in blood circulation that occur suddenly and last more than 24 hours, which is one leading cause of death in the world. One of the main risk factors of stroke is diabetes mellitus type 2. One complication is that when thrombosis occurs in the brain causing a stroke.Objective: This study aimed to determine the profile of type 2 diabetes mellitus in patients with acute thrombotic stroke who were treated in the Neurology Department at the Hospital Dr. Soetomo.Methods: Sampling was done with purposive sampling by observing the medical records of patients in the period of January 2014 to December 2015 based on inclusion and exclusion criterias that havebeen set.Results: Women with a history of type 2 diabetes are more exposed to acute thrombotic stroke; the age group which is most at risk for stroke is between age of 56-60 years; the average duration of DM until the occurence of stroke is 6,54 Â± 4,85 years; more than two-thirds of patients come to the hospital when the acute thrombotic stroke occurs with a condition of hyperglycemia; the most common comorbid disease is hypertension; and insulin therapy is the most widely used therapy in acute thrombotic stroke patients with type 2 diabetes.Conclusion: Managing the risk factors of stroke should prolong or prevent the incident of acute thrombotic stroke since most of the patients with type 2 diabetes mellitus came to the hospital with a condition of hyperglycemia and hypertension.